SuperMEN1 Pituitary, Parathyroid and Pancreas - Balogh, Katalin; Patocs, Attila; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
The vast expansion in research on tumorigenesis has greatly increased our understanding of tumor development in patients with inherited endocrine tumor syndromes. SuperMEN1, Pituitary, Parathyroid and Pancreas provides an up-to-date summary from clinical basics and latest follow-up guidelines to the most recent molecular findings in multiple endocrine neoplasia Type 1 syndrome. Articles have been assembled by acknowledged experts in their respective fields to provide current perspectives on the clinical and genetic backgrounds of this syndrome and to review carefully the latest discoveries concerning the possible functions and interactions of menin, the protein encoded by the MEN1 gene, including its possible role in cell cycle regulation, hematopoiesis, and bone development. The goal of this valume is also to present the most recent findings and the broadest aspects of the role of menin in tumorigenesis of the endocrine glands involved in MEN 1 syndrome (pituitary, parathyroid, endocrine pancreas and adrenal). The connection between the basic experimental and clinical points of view are highlighted through a discussion on animal models, which explores the field in both an inspiring and questioning manner with a focus on areas that remain to be clarified. Our goal was to bring together clinicians and basic researchers who represent a wide range of interests in this particular field of endocrine oncology. Presenting a comprehensive and current overview of basic experimental and clinical findings, this book can bring us closer to understanding endocrine tumorigenesis in multiple endocrine neoplasia Type 1.
MEN1 Clinical Background -- Genetic Background of MEN1: From Genetic Homogeneity to Functional Diversity -- Menin: The Protein Behind the MEN1 Syndrome -- Cellular Functions of Menin -- The Role of Menin in Hematopoiesis -- Role of Menin in Bone Development -- Activin, TGF-? and Menin in Pituitary Tumorigenesis -- The Role of Menin in Parathyroid Tumorigenesis -- Role of Menin in Neuroendocrine Tumorigenesis -- Adrenal Tumors in MEN1 Syndrome and the Role of Menin in Adrenal Tumorigenesis -- Functional Studies of Menin through Genetic Manipulation of the Men1 Homolog in Mice.
Keywords: Medicine; Biomedicine; Biomedicine general